Mechanism, risk, and solution of cultivated land reversion to mountains and abandonment in China - Xie, Zhen; Fan, Shenglong; Du, Shaorong; Zheng, Yong; Li, Chao (Frontiers in Environmental Science, 2023)
The cultivated land requisition-compensation balance (CLRB) system in China has been designed to defend cultivated land resources and grain production functions. Nevertheless, since the addition of a new policy, namely the linkage of increase and decrease (LID) of urban and rural construction land in 2008, a mass of cultivated land has been returning to mountains, sometimes resulting in abandonment. The county of Wannian was investigated from the microcosmic perspective, and we attempted to analyze the causes and risks employing the boosted regression trees (BRT) model and the grain productive capacity assessment model. The results indicate that (1) The compensatory cultivated land (CCL) has shifted uphill, with considerable fragmentation, from 2010 to 2020, and the abandonment rate reached 14.77%. (2) The factors of site condition, including elevation, patch area, and continuity of cultivated land, as well as a series of combinations, can explain the causes of abandonment. (3) The abandonment of these cultivated land areas eventually resulted in the risk of 297.48 t grain production capacity loss. The reason for the return of cultivated land to the mountains and its subsequent abandonment is the lack of consideration for the coupling relationship among site condition, use state, and function requirement, resulting in a spatial mismatch. Based on the findings, we propose a solution of the natural resources requisition-compensation balance (NRRB). To make up for the loss and reduce the risk, a spatial replacement was taken between the abandoned CCL in uphill and cultivable and available forest land (CAFL) in submontane areas, optimizing the spatial pattern of land use toward Von Thunen's agricultural circle.